2021
DOI: 10.3390/jcm11010105
|View full text |Cite
|
Sign up to set email alerts
|

Role of Clinical Characteristics and Biomarkers at Admission to Predict One-Year Mortality in Elderly Patients with Pneumonia

Abstract: Background: A hospitalization for community-acquired pneumonia results in a decrease in long-term survival in elderly patients. We assessed biomarkers at admission to predict one-year mortality in a cohort of elderly patients with pneumonia. Methods: A prospective observational study included patients >65 years hospitalized with pneumonia. Assessment of PSI, CURB-65, and biomarkers (C-reactive protein (CRP), procalcitonin (PCT), NT-pro-B-type natriuretic peptide (NT-proBNP), interleukin (IL)-6 and -8, tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
3
1
Order By: Relevance
“…CRP is a traditional marker of inflammation, which is low-cost, reproducible, and readily available in most settings. In our cohort, CRP at admission was not associated with mortality ( Malézieux-Picard et al, 2021 ), which is a finding already reported by others in different infectious diseases and settings ( Póvoa et al, 2011 ;Ryu et al, 2015 ). In a prospective study of adult patients with CAP (median age, 62 years), Chalmers et al found that a decrease of less than 50% of CRP levels at day 4 predicted an increased risk of 30-day mortality ( Chalmers et al, 2008 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…CRP is a traditional marker of inflammation, which is low-cost, reproducible, and readily available in most settings. In our cohort, CRP at admission was not associated with mortality ( Malézieux-Picard et al, 2021 ), which is a finding already reported by others in different infectious diseases and settings ( Póvoa et al, 2011 ;Ryu et al, 2015 ). In a prospective study of adult patients with CAP (median age, 62 years), Chalmers et al found that a decrease of less than 50% of CRP levels at day 4 predicted an increased risk of 30-day mortality ( Chalmers et al, 2008 ).…”
Section: Discussionsupporting
confidence: 84%
“…An association between high levels of proand anti-inflammatory cytokines (especially interleukin [IL]-1, -6, and -11) and CAP mortality has been described, but data in older patients are scarce ( Bacci et al, 2015 ;Guertler et al, 2011 ;Kellum et al, 2007 ;Pinargote-Celorio et al, 2020 ;Yende et al, 2008 ). In a recent study, we found no association between biomarkers of inflammation measured at admission and one-year mortality ( Malézieux-Picard et al, 2021 ). We aimed to explore whether the kinetics of inflammatory biomarkers during the index hospitalization and persistently elevated levels of biomarkers at discharge were predictive of one-year mortality in older patients hospitalized for pneumonia.…”
Section: Introductionmentioning
confidence: 62%
“…Interestingly, our results were consistent with the literature and showed that the suPAR seemed more accurate for prognostic purposes than other routinely used biomarkers, such as CRP and PCT. Previous studies reported that a weak nutritional status among elderly patients was a poor prognostic factor, speci cally a low BMI, which was a predictive factor of mortality, especially in the context of an infection [25]. In this cohort, BMI seemed to be associated with 30-day mortality, but this association was not statistically signi cant.…”
Section: Discussioncontrasting
confidence: 62%
“…CURB-65 is much less computationally time-consuming; however, it has a disadvantage in that it contains only five variables ( Buising et al, 2006 ; Capelastegui et al, 2006 ; Man et al, 2007 ). But in the cohort of elderly patients hospitalized for pneumonia in Geneva University Hospitals, the CURB-65 score was not predictive of one-year mortality ( Malézieux-Picard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%